Location system: site de mapeamento de locais de difícil acesso dos criadores de Aedes Aegypti - PINTO, Ricardo Junior da Silva (2024)
Due to the Brazilian region having a high incidence of rains and with that it generates accumulation of stagnant water. Thus, leading to the increase in the presence of dengue cases in Brazil, we sought to develop a website that would help to combat the increase in the breeding of Aedes Aegypti, the main causative agent of the diseases: dengue, Chikungunya and Zika. The site aims to support searches for places where ACS (community health workers) cannot reach. It has the help of drones that map the terrain and all the information is sent on the website that, through it, the health agencies responsible for endemic diseases will be informed of each location and will send endemic agents to take the appropriate measures. Thus, the site will have a direct synchronization with the competent health agencies.